2014
DOI: 10.5598/imafungus.2014.05.01.14
|View full text |Cite
|
Sign up to set email alerts
|

The Genera of Fungi: fixing the application of type species of generic names

Abstract: To ensure a stable platform for fungal taxonomy, it is of paramount importance that the genetic application of generic names be based on their DNA sequence data, and wherever possible, not morphology or ecology alone. To facilitate this process, a new database, accessible at www.GeneraofFungi.org (GoF) was established, which will allow deposition of metadata linked to holo-, lecto-, neo- or epitype specimens, cultures and DNA sequence data of the type species of genera. Although there are presently more than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 64 publications
5
65
0
Order By: Relevance
“…Hyde, in Ariyawansa et al, Fungal Diversity: 75(1): 105 (2015) The genus Galliicola was introduced in the family Phaeosphaeriaceae to accommodate a bitunicate ascomycete saprobic on a Galium species ). Notes -Wojnowicia dactylidicola was introduced by Liu et al (2015), however recent phylogenetic studies showed the ex-type strain of W. dactylidicola (MFLUCC 13-0738) clustered outside of the genus (Crous et al 2015). In the present phylogenetic analysis, W. dactylidicola forms a sister clade to Galiicola pseudophaeosphaeria (MFLUCC 14-0524).…”
Section: Allophaeosphaeria Muriformiamentioning
confidence: 49%
See 3 more Smart Citations
“…Hyde, in Ariyawansa et al, Fungal Diversity: 75(1): 105 (2015) The genus Galliicola was introduced in the family Phaeosphaeriaceae to accommodate a bitunicate ascomycete saprobic on a Galium species ). Notes -Wojnowicia dactylidicola was introduced by Liu et al (2015), however recent phylogenetic studies showed the ex-type strain of W. dactylidicola (MFLUCC 13-0738) clustered outside of the genus (Crous et al 2015). In the present phylogenetic analysis, W. dactylidicola forms a sister clade to Galiicola pseudophaeosphaeria (MFLUCC 14-0524).…”
Section: Allophaeosphaeria Muriformiamentioning
confidence: 49%
“…(1889) Septoriella is an asexual genus that is commonly distributed on grasses. The genus is characterized by pycnidial, unilocular conidiomata and fusiform to subcylindrical, euseptate, pale brown, conidia bearing mucoid appendages at both ends (Crous et al 2015, Li et al 2015. Crous et al (2015) reduced to synonymy Wojnowicia with Septoriella, but we recognized Wojnowicia as a separate genus (Fig.…”
Section: Poaceicola Italicamentioning
confidence: 91%
See 2 more Smart Citations
“…These fungi are treated as Ascomycota, genera incertae sedis. Nevertheless, several recent studies have re-collected historic genera, subjected then to morpho-molecular analyses and provided taxonomic placements (Dai et al 2014, Wijayawardene et al 2013, Crous et al 2015a. Seifert et al (2011), Hyde et al (2013), Johnston et al (2014), Wijayawardene et al (2014Wijayawardene et al ( , 2017, Maharachchikumbura et al (2015, Rosman et al (2013Rosman et al ( , 2015aRosman et al ( , b, 2016, Réblová et al (2015Réblová et al ( , 2016 and Senanayake et al (2015) have provided significant taxonomic and nomenclatural changes for different taxonomic groups based on DNA sequence analyses.…”
Section: Introductionmentioning
confidence: 99%